2019
DOI: 10.1177/1359105319877298
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic outcomes related to depression in adults with type 1 diabetes

Abstract: Glycemic outcomes of adults with type 1 diabetes may be affected by depression. Our aim was to compare outcomes of “depressed” (Patient Health Questionnaire-9 ⩾ 10, N = 83) to “not-depressed” matched control (Patient Health Questionnaire-2 < 3, N = 166) adults with type 1 diabetes with objective measures. The depressed group had poorer blood glucose control and, for those with glucose meter downloads, fewer glucose tests/day. The groups did not differ on glucose variability or episodes of hypoglycemia. Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Regarding the association between glycemic control and depressive symptoms in T1DM and T2DM, a significant relationship was found in both groups, which is in accordance to what has been reported in the literature (Egbuonu et al, 2019;Park et al, 2004;Picozzi & DeLuca, 2019;Santos et al, 2013). Nevertheless, in other studies, depressive symptoms and glycemic control did not show a clinically significant association (Braz et al, 2012;Fisher et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the association between glycemic control and depressive symptoms in T1DM and T2DM, a significant relationship was found in both groups, which is in accordance to what has been reported in the literature (Egbuonu et al, 2019;Park et al, 2004;Picozzi & DeLuca, 2019;Santos et al, 2013). Nevertheless, in other studies, depressive symptoms and glycemic control did not show a clinically significant association (Braz et al, 2012;Fisher et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence rates for depression were more than 3-fold higher in people affected by T1DM (12%, range 5.8–43.3% vs. 3.2%, range 2.7–11.4%) and up to 2-fold higher in those with T2DM (19.1%, range 6.5–33% vs. 10.7%, range 3.8–19.4%) vs. healthy controls; in all cases (T1DM, T2DM, and healthy controls), higher rates of depression were observed in women compared to men ( 14 ). Moreover, other studies focusing on the comorbidity between depression and T1DM reported an inconsistency in prevalence rates, although confirming the close relationship between depression and poor glycemic control and lack of self-care in diabetic patients ( 18 , 19 ). Fisher et al suggested that the cause of these discrepancies may lie in a methodological issue associated with a difficulty to distinguish between a depressive state and emotional distress linked to management of the chronic disease ( 20 ).…”
Section: Introductionmentioning
confidence: 60%
“…Specifically, no association was revealed with HbA 1 c levels. There are conflicting data in literature regarding the link between indicators of glycemic compensation and depression, with some studies that highlight a poorer compensation in depressed subjects ( 19 ) and others that do not ( 40 , 57 ). It is worthy of note that in comparison with other studies in which indicators of metabolic compensation and levels of depression were evaluated contextually ( 19 ), in the present study HbA 1 c levels related to the last control undertaken over the previous 3 months, whilst the reference time frame for assessment of depression using the BDI-IA scale was the previous 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations